0

# What is the substitution method for -x y-2?

Updated: 4/28/2022

Wiki User

10y ago

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".

It is not at all clear what is required to answer this question.

Wiki User

10y ago

Earn +20 pts
Q: What is the substitution method for -x y-2?
Submit
Still have questions?
Related questions

### What is y to the 8th power as an product in four different was with only positive exponents?

y6 x y2 y4 x y4 y2 x y2 x y4 y2 x y2 x y2 x y2

x+y=5

### Use the substitution method to solve the system of equations Enter your answer as an ordered pair?

Use the substitution method to solve the system of equations. Enter your answer as an ordered pair.y = 2x + 5 x = 1

0

### Solve this using substitution x plus 2y equals 30 x2 plus y2 equals 900?

x+2y = 30 =&gt; x= 30-2y x2+y2 =900 (30-2y)2+y2 = 900 (30-2y)(30-2y)+y2 = 900 900-60y-60y+4y2+y2 = 900 5y2-120y = 0 y(5y-120) = 0 y = 0 or y= 24 Substitute the value of y into the original equations to find the value of x: Therefore: x = -18 and y = 24 Check: -18+48 = 30 and (-18)2+242 = 900

Yes, as x-y2=0

### Which technique of differentiation does the substitution method attempt to undo?

The substitution method undoes the chain rule.

### What is y6x plus 11 y2x plus 7 in substitution method?

If you mean: y = 6x+11 and y = 2x+7 Then by substitution: x = -1 and y = 5

### What is the answer to (x plus y)2 x2 plus y2?

X2+y2=25 (x-8)2+y2 =41

2x-3y=13

### How do you solve x plus y equals 4 and y equals 2X plus 1 by substitution method?

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 =&gt; 3 = 3x =&gt; 1 = x So by substitution: x = 1 and y = 3

### Convert x2 plus y2 equals 2x?

What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x &there4; y2 = 2x - x2 &there4; y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x &there4; x2 - 2x = -y2 &there4; x2 - 2x + 1 = 1 - y2 &there4; (x - 1)2 = 1 - y2 &there4; x - 1 = &plusmn;(1 - y2)1/2 &there4; x = 1 &plusmn; (1 - y2)1/2